The Long-Term Effect of Cattle Manure Application on Soil P Availability and P Fractions in Saline-Sodic Soils in the Songnen Plain of China - Xiaotong Feng; Changjie Liu; Yang Li; Jiaqi Xu; Juan Zhang; Qingfeng Meng (Agronomy)
Lower soil phosphorus (P) availability in saline-sodic soils is due to high pH and salinity, which seriously limited crop growth. Manure application has a positive effect on soil properties and P availability. We conducted an experiment, which included five treatments with different durations of manure application: 11-, 16-, 22-, and 27-year manure treatments, and no manure as a control treatment (CK). The results showed that manure application decreased soil pH and electrical conductivity (EC) and increased soil organic matter (SOM). Soil available P content increased by 236.76 mg·kg−1 after applying manure for 27 years. Compared to the CK treatment, manure application significantly increased alkaline phosphatase (ALP) 3.36–6.05-fold and increased microbial biomass phosphorus (MBP) 3.69–15.90-fold (p < 0.05). The organic P (Po) and inorganic P (Pi) contents increased with manure application, except Ca10-P and O-P. Furthermore, we found that pH and EC were significantly negatively correlated with SOM (p < 0.05). MBP and ALP were significantly positively correlated with SOM (p < 0.05). Available P was mainly affected by Ca2-P (+0.71, p < 0.001). Overall, manure application in saline-sodic soils altered soil saline-sodic properties by increasing SOM. The results also indicated that enhanced soil available P is due to an increase in Ca2-P, Al-P, and Po mineralization, especially for Ca2-P.